2009
DOI: 10.1128/iai.00892-08
|View full text |Cite
|
Sign up to set email alerts
|

Antibody to the Type 3 Capsule Facilitates Immune Adherence of Pneumococci to Erythrocytes and Augments Their Transfer to Macrophages

Abstract: Streptococcus pneumoniae has been shown to bind to erythrocytes via a process called immune adherence. This adherence and the subsequent transfer of pneumococci from erythrocytes to macrophages are both dependent on complement C3 deposition onto the pneumococcal surface. The observation that anti-capsule antibody increases C3 deposition on the pneumococcal capsule indicated that anti-capsule antibody may also facilitate the clearance of pneumococci through immune adherence. Using pneumococcal strain WU2 (capsu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 44 publications
1
20
0
Order By: Relevance
“…In light of these tenets and previous work which demonstrated that A7 is not opsonic in vitro (14) and requires C3 to mediate protection in mice (10), our data suggest that the mechanism by which A7 mediates protection in vivo is by promoting C3 deposition on the ST3 capsule. Clearance of C3-opsonized bacteria is enhanced in vivo (4,5), and immune adherence of C3-opsonized bacteria to red blood cells via complement receptors is thought to enhance intravascular clearance to the reticuloendothelial system (20,32,33). The phenomenon of immune adherence has been reported for PPS-specific IgG, but to our knowledge, it has not been demonstrated for IgM.…”
Section: Discussionmentioning
confidence: 76%
“…In light of these tenets and previous work which demonstrated that A7 is not opsonic in vitro (14) and requires C3 to mediate protection in mice (10), our data suggest that the mechanism by which A7 mediates protection in vivo is by promoting C3 deposition on the ST3 capsule. Clearance of C3-opsonized bacteria is enhanced in vivo (4,5), and immune adherence of C3-opsonized bacteria to red blood cells via complement receptors is thought to enhance intravascular clearance to the reticuloendothelial system (20,32,33). The phenomenon of immune adherence has been reported for PPS-specific IgG, but to our knowledge, it has not been demonstrated for IgM.…”
Section: Discussionmentioning
confidence: 76%
“…The ability of IgM in serum to bind to pneumococci was determined by an in vitro IgM-binding assay as described previously (11). Bacteria frozen stock was washed twice in PBS and centrifuged at 4,000 ϫ g for 6 min.…”
Section: Methodsmentioning
confidence: 99%
“…The ST3 S. pneumoniae WU2 strain was grown in tryptic soy broth (TSB) to mid-log phase as described previously (49). WU2 has been used extensively to study the host response to and survival after infection with ST3 in mice (6,26,30,37,48,49,54). Purified PPS3, isolated from strain 6303 and obtained from the American Type Culture Collection, was used for enzyme-linked immunosorbent assay (ELISA)-based analyses of MAb binding.…”
Section: Methodsmentioning
confidence: 99%